Television news the heart and how-to of video storytelling - Keller, Teresa (Routledge, Taylor & Francis Group, 2019)
"Television News is a comprehensive resource for newswriting, reporting, shooting and editing video, and producing a newscast. This book provides instruction in the basic steps of telling video stories, and is perfectly suited for preparing young professionals for entry-level positions as a television or multimedia journalist. Moreover, the text goes to the heart of storytelling with guidance appropriate for advancement in an industry that is challenged more than ever to retain the public trust. The reporting and video storytelling skills found in this book can also be applied in non-traditional video communication jobs in both businesses and nonprofits. Conversational and easy to understand, this book grounds readers in the ethical and legal consideration necessary to do the job right. New to the fourth edition is coverage of social media, shooting and broadcasting with mobile phones, and a discussion of "fake news." This book can be used in stand-alone introductory broadcast courses or across multiple, specialized modules. It features a website with ancillary material that helps students learn to write, shoot, and edit video with practical activities"--